Neurosains Dalam Komunikasi Dakwah - Rezsa Yushardiansyah (Moderasi : Journal of Islamic Studies, 2022)
Da'wah science is a very dynamic science and can continue to grow where it can be observed through the nature of the study of communication through a wider paradigm and dimension, namely through the scientific perspective of Neuroscience. The study of cognitive neuroscience in this study aims to be related to interest and an effort to find supporting factors that can optimize the process of delivering information and receiving messages related to its functionality for the purpose and interests of da'wah activities and sciences so that the correlation of understanding becomes more convergent through the substance of various scientific pieces of literature, especially deepening. Neuroscience studies (Central Nervous System). The theory used in this study is a theory of the study of the Neuroscience area related to the processing of information, where the main review of this study is to find out and study the biological basis of each behavior or action